Early childhood educators reflect on their conversations with parents about children's diverse gender expression - Sarah Reddington (Brock University, 2023)
This research captures early childhood educators (ECEs) perspectives when communicating with parents about their children's diverse gender expression. Since families and ECEs play a pivotal role in shaping young children's understandings of gender, there is requirement to learn more about ECEs communications with parents. The research that informs this paper is derived from semi-structured focus groups with 15 ECEs who work with young children, ages 3-5 years, at regulated early childhood centers in Halifax, Nova Scotia, Canada. It explores the reflections from ECEs after having conversations with parents whose children identify outside the traditional constructs of masculine boy/ feminine girl. One central finding the ECEs observe is the displeasure fathers have when their sons engage in feminine interests, including the affective actions the fathers then take to regulate and remove stereotypical girl activities from their sons' lives. This research highlights the need for more early childhood education training on gender diversity to better support non-binary, transgender children, and children from LGBTQ families and future collaboration with families.